(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The Motion analysis is used to solve problems which related to the learning and training.in addition, It diagnoses movements, compares their parts, times and strengths, and compares between good and bad movement, as well as It helps to develop the movement and its performance. There are few studies in of motion analytical for study, The researcher design this study in a scientific procedure by using the scanner device (Gait Analysis) of the German company (Zebris)to read the data in a standardized manner during the test, the researcher selected the sample of the Iraqi champions in the competition of (100 m and 1500 m and 5000 m )Two for each contest in a deliberate way. for the heroes of Iraq and the number of them six, two for each contest. for the Time period from 11/9/2018 to 1/12/1018, in the laboratory of physical mechanics in the Faculty of Physical Education and Sports Sciences / University of Kufa. The search variable was chosen maximum force because it has a large role in the movement and transfer of athletic during the race, Concluded researcher to The maximum amount of force distributed on the footprint (front, center and heel) and according to the requirements of the race, and The higher the speed and force.